Failure to launch - McConaughey, Matthew, 1969-; Parker, Sarah Jessica; Deschanel, Zooey, 1980-; Bartha, Justin; Cooper, Bradley; Bradshaw, Terry; Bates, Kathy, 1948-; Rudin, Scott, 1958-; Aversano, Scott; Astle, Tom J.; Ember, Matt.; Dey, Tom.; et al. (Hollywood, Calif. : Paramount Pictures, 2006)
Tripp is a thirtysomething slacker, but that doesn't mean that he is ready to give up the many benefits of living at home with his mom and dad. His desperate parents have had enough though, and after years of gentle nudging they soon realize that it is going to take a concerted effort to get Tripp out so they can enjoy their twilight years in peace. Realizing that their only hope for riding themselves of their reluctant-to-leave son, Al and Sue hope that on the off-chance Tripp will meet the woman of his dreams, the two enlist the help of a beautiful and talented woman in providing the romantic incentive needed to finally get their son out of the family home.
Cast: Matthew McConaughey, Sarah Jessica Parker, Zooey Deschanel, Justin Bartha, Bradley Cooper, Terry Bradshaw, Kathy Bates.
Director of photography, Claudio Miranda ; editor, Steven Rosenblum ; music, Rolfe Kent ; costume designer, Ellen Mirojnick ; production designer, Jeremy Conway.
MPAA rating: PG-13; for sexual content, partial nudity and language.
Region 1 ; Dolby Digital 5.1 surround.
Languages: English or French ; subtitles: English or Spanish.
Some copies have closed captioning for the hearing impaired.
Keywords: Single men -- Conduct of life -- Drama; Man-woman relationships -- United States -- Drama; Dating (Social customs) -- United States -- Drama; Romantic comedy films; Video recordings for the hearing impaired